2021
DOI: 10.4088/jcp.20m13458
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between ADHD Medication Use in Pregnancy and Severe Malformations Based on Prenatal and Postnatal Diagnoses

Abstract: Objective: Attention-deficit/hyperactivity disorder (ADHD) medications are increasingly used in pregnancy. Studies on the pregnancy safety of these medications that are restricted to live births may underestimate severe teratogenic effects that cause fetal demise or termination of pregnancy. The present study addresses this limitation by including data from both prenatal and postnatal diagnoses of major malformations. Methods: A nationwide registry-based study was conducted of 364,012 singleton pregnancies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The current study took advantage of a collaboration within the InPreSS consortium, which aims at pooling data from the 5 Nordic countries (Denmark, Finland, Iceland, Norway, and Sweden) and the US to increase statistical precision in pregnancy safety studies. Our study overlaps with previous studies using Swedish and Danish data 7,12,13 to some extent, but with its multicountry approach is significantly larger. Nevertheless, it was still limited by imprecise risk estimates.…”
Section: Strengths and Limitationssupporting
confidence: 40%
See 1 more Smart Citation
“…The current study took advantage of a collaboration within the InPreSS consortium, which aims at pooling data from the 5 Nordic countries (Denmark, Finland, Iceland, Norway, and Sweden) and the US to increase statistical precision in pregnancy safety studies. Our study overlaps with previous studies using Swedish and Danish data 7,12,13 to some extent, but with its multicountry approach is significantly larger. Nevertheless, it was still limited by imprecise risk estimates.…”
Section: Strengths and Limitationssupporting
confidence: 40%
“…Data on the potential teratogenicity of in utero exposure to atomoxetine, a selective norepinephrine reuptake inhibitor also used to treat ADHD, 9,10 are very limited. 11 Two studies 7,12 that reported on atomoxetine as one ADHD medication of several in a variable defined by exposure to any ADHD medication raised no concerns, and likewise for a recent study 13 that reported separately on atomoxetine and the risk of major malformations in general. In studies of rabbits and rats, 14 high doses of atomoxetine (25-100 mg/kg/d compared to the recommended dose in humans of 1.2-1.8 mg/kg/d) have been associated with reduced fetal and postnatal viability in rodents, particularly with increased frequency of cardiovascular malformations and incomplete ossification of bones.…”
mentioning
confidence: 99%
“…(2018) suggest a small increase in the risk of cardiac malformations associated with intrauterine exposure to MPD [19]. Kolding et al found that exposure to MPD was associated with an increased risk of cardiac malformations in particular ventricular septal defects [15]. The possible association with gastroschisis, omphalocele and transverse limb deficiency has to be investigated further [14].…”
Section: Tablementioning
confidence: 99%
“…ADHD medication use in early pregnancy may be associated with an increased risk for birth defects such as gastroschisis, omphalocele, and transverse limb deficiency [14]. ADHD medication such as MPD also seemed to be associated with an small but elevated risk of cardiac malformations when taken in first trimester [15,16]. On the other hand several large studies showed no major malformations when MPD was taken by pregnant patients [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These analyses found no differences in overall risk of major malformations after exposure to mixed amphetamine salts or methylphenidate. [10][11][12] Spontaneous abortion (miscarriage) has also been associated with in utero exposure to methylphenidate. 7,13,14 Considering obstetrical and neonatal complications, stimulants have been associated with increased risk of hypertensive disorders, 15 preeclampsia, 16 placental abruption, 16 small for gestational age fetal growth, 16 preterm birth, 10,16,17 and requirement for neonatal intensive care unit level of care.…”
mentioning
confidence: 99%